Luxembourg : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper analyzes economic developments in Luxembourg during the 1990s. Economic performance continues to be exceptional in Luxembourg. Growth averaged 6 percent during 1980s, well above the European average, while the inflation and unemployment rates ranked among the very lowest. In 1994, Luxembourg was the only European industrialized country to run a general government surplus. Luxembourg also had the lowest debt-to-GDP ratio, the largest current account surplus, and possibly the highest real saving in this group. These successes are attributable at least in part to the skillful management of policy to facilitate structural change.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet